Enhanced Stability and Conductivity of (polyaniline/chitosan) Composites - Ratuchne, Fernando; Danczuck, Marins; de Castro, Eryza Guimarães (Orbital: The Electronic Journal of Chemistry, 2018)
This study describes the synthesis of Pani-Chitosan soluble hybrid composite through an in situ polymerization of aniline in hydrochloride acid media in the presence of chitosan. The optical, morphological, structural, thermal and electrochemical characteristics of these materials were studied by UV–Vis, FTIR, SEM, TG and CV analysis. From UV-Vis and FTIR, the formation of composite was confirmed. The SEM images show that Pani presented agglomerate morphology, while Pani-Chitosan composite shows plate-like morphology, with higher surface area and the TG results showed that Pani-Chitosan has greater thermal stability. The electrochemical measurements indicate that Pani-Chitosan material presents upper current density at all scan rates studied, sharper and shifted peaks to more negative potentials, indicating that the charge injection processes are easier. These results indicate that the composite material is promising for application in electrochromic devices and capacitors, because of its greater surface area, thermal and electrochemical stability. DOI: http://dx.doi.org/10.17807/orbital.v10i3.1110